Determining K+ channel activation curves from K+ channel currents often requires the Goldman-Hodgkin-Katz equation - Clay, john r. (Frontiers in Cellular Neuroscience, 2009)
Potassium ion current in nerve membrane, IK, has traditionally been described by IK = gK(V-EK), where gK is the K ion conductance, V is membrane potential, and EK is the K+ Nernst potential. This description has been unchallenged by most investigators in neuroscience since its introduction almost sixty years ago. The problem with the IK (V-EK) proportionality is that it is inconsistent with the unequal distribution of K ions in the intra- and extracellular bathing media. Under physiological conditions the intracellular K+ concentraion is significantly higher than the extracellular concentration. Consequently, the slope conductance at potentials positive to EK cannot be the same as that for potentials negative to EK, as the linear proportionality requires. Instead IK has a non-linear dependence on (V-EK) which is well described by the Goldman-Hodgkin-Katz equation. The implications of this result for K+ channel gating and membrane excitability are reviewed in this report.